Aproximación teórica a la incidencia de los juegos tradicionales en el desarrollo físico de niños de 12 años de la unidad educativa Francisco Martínez Aguirre del Cantón Vinces. - MENDOZA ARIAS HAYDY MICHEL (2024)
This study aimed to analyze the potential impact of traditional games on the physical development of 12-year-old children at the Francisco Martínez Aguirre Educational Unit in the Vinces Canton. The research addressed the need to understand how traditional games could contribute to physical development in a context where promoting physical activity was crucial to combat sedentary lifestyles and improve children's health. A mixed-methods approach was employed, combining quantitative and qualitative methods to obtain a comprehensive understanding of the phenomenon. The quasi-experimental design allowed for the observation and measurement of the impact of traditional games without directly manipulating the variables. Structured surveys and direct observations were used as data collection techniques, with specific instruments such as closed-ended questionnaires. The study population consisted of 68 12-year-old children, and a probabilistic sample of approximately 58 children was selected to ensure adequate representation. The collected data were analyzed using statistical software such as Excel, enabling the transformation of data into understandable information through graphs and tables. The expected results of this research contributed to the formulation of educational and health policies that integrated traditional games as an effective tool for children's physical development. The aim was to demonstrate that these playful activities not only preserved cultural heritage but also promoted the physical and emotional well-being of students, facilitating their overall development in a school environment.